1993
DOI: 10.1046/j.1365-313x.1993.t01-5-00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Gametophytic and sporophytic expression of an antherspecific Arabidopsis thaliana gene

Abstract: Genomic and cDNA clones of the anther-specific APG gene from Arabidopsis thaliana and Brassica napus, which encodes a novel proline-rich protein, were isolated and characterized. Southern blotting and Northern analysis of male fertile and cytoplasmic male sterile varieties of B. napus showed that the APG gene is present as a single copy in the Arabidopsis genome, and that the B. napus APG gene is a member of a small anther-specific gene family. Analysis of developmentally staged B. napus flower buds indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It was reported that APG transcript was confined to anther during microspore development in Brassica. napus flower buds [87]. It was also suggested that five APG genes in Silene latifolia were related to anther fertility, which were required for development of fertile pollen [88].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that APG transcript was confined to anther during microspore development in Brassica. napus flower buds [87]. It was also suggested that five APG genes in Silene latifolia were related to anther fertility, which were required for development of fertile pollen [88].…”
Section: Resultsmentioning
confidence: 99%
“…The present analysis also has reported some unexpected results. As an example, anther-specific proline-rich protein APG transcripts have been found in the pistil, when they have been considered to be confined to the anther during the period of microspore development, with a dramatic decline during pollen maturation (Roberts et al, 1993 ). This result could be explained by the implication of the proline-rich protein APG in the pollen tube during the germination process, through a process yet to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these proteins were of unknown functions and have less than a 50% similarity (30% identity) with the cabbage protein. Among the proteins, functionally-characterized proteins include the Arabidopsis lipase Arab-1 (Brick et al, 1995), Brassica napus myrosinaseassociated proteins (Taipalensuu et al, 1997), anther-specific proline-rich proteins APG in Arabidopsis and CEX in B. napus (Roberts et al, 1993), extracellular lipase EXLs in Arabidopsis pollen coat (Mayfield et al, 2001), Medicago nodule-specific protein (Dickstein et al, 1993), Medicago pollen-specific coil protein PO22 (Wu et al, 1996), and Digitalis lanatoside O-acetylesterase (Kandzia et al, 1998). Among the bacterial enzymes that have been functionally characterized, lipases from Aeromonas hydrophila and Vibrio parahaemolyticus share homology with the cabbage protein, although the % similarity is much lower.…”
Section: Isolation Of a Chinese Cabbage Lipase-like Protein Genementioning
confidence: 99%